2015
DOI: 10.5762/kais.2015.16.5.3333
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Related to Substance Use among Korean Adolescents: Focusing on Sexual Experiences and Risky Sexual Behaviors

Abstract: The purpose of this study is to investigate factors related to substance use focusing on the sexual experiences and risky sexual behaviors among Korean adolescents. This study conducted with a secondary data analysis using the Seventh Korea Youth Risk Behavior Web-based Survey 2011 in South Korea. The study participants selected 75,643 Korean adolescents who were recruited anonymously through national web-based survey. Data were analyzed using descriptive statistics, rao-Scott χ 2 , and logistic regressions co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Additionally, adolescents are still immature in regard to taking responsibility for sexually transmitted diseases and pregnancy that may occur after a sexual experience [ 20 ]. Adolescents’ sexual experience starts from curiosity and tends to occur simultaneously with drinking and smoking [ 21 ]. That is, it is related to the problem behavior of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, adolescents are still immature in regard to taking responsibility for sexually transmitted diseases and pregnancy that may occur after a sexual experience [ 20 ]. Adolescents’ sexual experience starts from curiosity and tends to occur simultaneously with drinking and smoking [ 21 ]. That is, it is related to the problem behavior of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is worrying, given the increased risk of neurological impact (Brown, Tapert, Granholm, & Delis, ) and future alcohol dependence (Hawkins, Catalano, & Miller, ) that younger consumption predicts. Specific risk factors for adolescent substance abuse in Korea include being male, poor performance in school, and lower socioeconomic status (Park & Jeon, ), and there is evidence that peer groups play an influential role in alcohol consumption (Nakashima & Wong, ). Korean adolescents have reported that reduction of depression, anger, and anxiety were the primary reasons they drank (Park & Jeon, ).…”
Section: Substance Use In Koreamentioning
confidence: 99%
“…Specific risk factors for adolescent substance abuse in Korea include being male, poor performance in school, and lower socioeconomic status (Park & Jeon, ), and there is evidence that peer groups play an influential role in alcohol consumption (Nakashima & Wong, ). Korean adolescents have reported that reduction of depression, anger, and anxiety were the primary reasons they drank (Park & Jeon, ). Teenage alcohol use is a top risk factor for later suicide ideation and attempts, which is particularly notable considering the 40.7% increase in adolescent suicide mortality that occurred between 2000 and 2006, according to the Korean National Statistical Office (Kim & Kim, ).…”
Section: Substance Use In Koreamentioning
confidence: 99%
“…For example, obviously, social support was considered as one of the situational factors that impact on functional status (Lenz et al, 2014). A crosssectional study by Park and Shin (2017) found that social support was associated with ability to perform individual functioning among patients with liver cirrhosis such as preparing food, exercising regularly, and administering medication (r= 0.80, p<0.001). Youssef (2013) noted that social support was significantly associated with many dimensions of health-related quality of life including physical, psychological, social, and role functioning (r = 0.21, p= 0.0005) among persons with liver cirrhosis.…”
Section: Introduction Background and Significance Of The Studymentioning
confidence: 99%